2020
DOI: 10.1002/mma.6673
|View full text |Cite
|
Sign up to set email alerts
|

Well posedness and stability result for a thermoelastic laminated Timoshenko beam with distributed delay term

Abstract: In this work, we consider a linear thermoelastic laminated timoshenko beam with distributed delay, where the heat conduction is given by cattaneoâs law. we establish the well posedness of the system. For stability results, we prove exponential and polynomial stabilities of the system for the cases of equal and nonequal speeds of wave propagation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…The distributed delay is very important in these problems, and it has been studied in many issues, for example, previous works 6,15‐19 . From this absolute, adding the distributed delay limit makes the problem different from previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…The distributed delay is very important in these problems, and it has been studied in many issues, for example, previous works 6,15‐19 . From this absolute, adding the distributed delay limit makes the problem different from previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the control of PDEs with time delay effects has become an active area of research (see, for example, [15,[20][21][22][23][24][25][26][27]). In many cases, it was shown that delay is a source of instability unless additional condition or control terms are used; the stability issue of systems with delay is of theoretical and practical great importance.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the time or delay recorded in many natural and physical phenomena, especially problems resulting from vibrations, is an important factor for stability in general. And it has been studied extensively by many authors, including [5][6][7][11][12][13][14][15][16][17][18][19][20][21]. Recently, in the presence of the varying delay, Mezouar and Boularrass studied system (1); for more information, see [22].…”
Section: Introductionmentioning
confidence: 99%